At-Ta’min at-Ta’awuni fi Manzuri al-Fiqh al-Islamiy - Bakri, Wahyudi (Islamic Economics Journal, 2013)
This study analyzes the effect on income tenants muzara’ah through case study in modern Islamic Boarding School Gontor Mantingan Ngawi. The tool of analysis used to determine the factors affecting farmers’ income is multiple linear regression. From the analysis of the factors that affect rice production is obtained that the area of land, seed, fertilizer, pesticides and HOK jointly have a significant effect on rice production. The use of production factors such as land, fertilizer and pesticides showed positive and significant effect on rice production, while the use of production factors such as seed and HOK showed no significant effect. These factors together showed a significant effect on rice production. Average land to expand production at one time the plant is 6123 kg/ha. From the analysis of data, known to the average revenue yield of the rice paddies are 18.369.000/ha reduced total cost of planting one of 7.801.716,63/ha, we got the result of 10.567.283,37. Because it uses the system muzara’ah the results are shared with the foundation so that the two net income of farmers amounted to Rp. 5.283.641,685/ha. The results of data analysis influence of the productivity of smallholder farmers net income showed a positive and significant impact on net income of farmers.